A Comparative Study of Active and Passive Adverse Drug Reaction Reporting Systems in Terms of False Reporting Rate - Bansal, Alka; Agrawal, Ashish; Sharma, Lokendra; Jain, Smita (Scripta Medica, 2020)
Background: World Health Organisation Uppsala Monitoring Centre (WHO-UMC) was set up in 1968 to collect Adverse Drug Reactions (ADRs) periodically for all drugs across the globe. It identifies two main approaches to pharmacovigilance: active (intensive) and passive (spontaneous). However, very few studies are available to compare these two methods of adverse drug reaction reporting.Methods: A prospective observational study was done on 303 newly diagnosed patients with tuberculosis receiving directly observed therapy short-course (DOTS) in the Sawai Man Singh (SMS) Hospital, Jaipur between 1 January 2019 and 31 December 2019. They were randomly divided into groups A (150 patients) and B (153 patients). Group A patients were followed actively at fixed intervals of time for ADRs till next six months through electronic conversation or personal interview. Group B patients were required to report spontaneously for any ADRs to pharmacovigilance centre. After data collection causality assessment was done using the WHO-UMC scale to identify false reporting and finally results were analysed statistically by means of the t-test using Minitab 14 software Pennsylvania, USA.Results: 153 ADRs were reported in active and 39 in passive group. Hence the yield of ADR was four times more in active method. After causality assessment, 31 in group A and 12 in group B were found to be falsely related (unlikely) to antitubercular drugs. Two sample t-test revealed active method reported more false ADR (p = 0.005).Conclusion: Although active method of surveillance identifies more ADRs than passive method, it is also more prone to false reporting. Hence its benefits should be weighed against its cost before adopting it for countries with limited resources.
Keywords: Neželjene reakcije na lekove; Sistemi za izveštavanje; Tuberkuloza; Farmakovigilancija